PENGELOMPOKKAN KABUPATEN/KOTA DI INDONESIA BERDASARKAN MASALAH GIZI BALITA DENGAN MENGGUNAKAN METODE TWO STEP CLUSTER DAN ENSEMBLE CLUSTERING - Cichi Chelchillya Candra; Ferra Yanuar; Dodi Devianto (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to group districts/cities in Indonesia based on toddler nutrition problems.. The research method used in this research is Two Step Cluster, Fuzzy C-Means and K-Modes method. In the Two Step Cluster method, there are two stages carried out, namely Pre-Clustering and Case of Clustering. In the Ensemble K-modes method, there are two methods, namely Fuzzy C-Means and K-Modes. The data used in this study are secondary data in the form of data on under-five nutrition problems in Indonesia in 2022. After analysis, the grouping results obtained using the Two Step Cluster method consist of 2 clusters, while the Ensemble K-modes method produces 5 clusters